Reforming Tax Law Enforcement: The Role of Core Tax Administration System Digitalization and the Ultimum Remedium Principle - Bambang Djinarto; Slamet Suhartono; Syofyan Hadi; Sri Setyadji; Juan Nickalus (Journal of Law and Legal Reform)
This study aims to analyze the impact of the digitalization of the Core Tax Administration System (CTAS) on tax law enforcement, with a particular focus on the application of the ultimum remedium principle. The research method employed is normative legal research, involving an in-depth analysis of tax law literature, relevant regulations, and case studies of CTAS implementation. The urgency of this research lies in addressing inefficiencies, inequities, and the lack of transparency in traditional tax law enforcement through the utilization of digital technology. The findings reveal that CTAS digitalization enhances efficiency, transparency, and data management in tax administration while strengthening law enforce ment processes through improved oversight and compliance. However, this digitalization also presents challenges, including data security risks, privacy concerns, and compliance with applicable regulations. The novelty of this research lies in integrating the ultimum remedium principle within the digital framework, advocating for a proportional approach to tax violations by prioritizing voluntary compliance and corrective measures before escalating to more severe enforcement actions. This study provides strategic contributions to legal policy development, offering essential insights for policymakers, legal practitioners, and system developers in designing a tax law enforcement system that is fair, transparent, and responsive to the demands of the digital era.